Caracterização de sedimento e de contaminantes numa microbacia hidrográfica antropizada - Gonçalves, Celso Silva (2007)
The agricultural activities generate an impact on the environment that needs constant study to improve the understanding of the ways, levels and implantation of litigator practices of contamination. The study of contaminants in drainage water from hydrographic water shed is indicated because the ways of contamination can be well done identified. In this sense, this work was organized to study a hydrographic water shed of head in Agudo , RS, Brazil, with a purpose to investigate the land occupation and pollution process, characterize the mineralogy of eroded sediments, study the phosphorus dynamic present in surface material, and identify the presence of the main pesticides molecules used in the tobacco culture. Tobacco is the main culture in the hydrographic watershed occupying 74% of the designated area for annual cultures. The conventional practice of tobacco culture generates furrows and interfurrows erosion in almost all farming area. The annual culture occupies chernosols and regosols that are the mainly suppliers of suspended sediments being 90% of clay minerals 2:1, as smectite. The sediment and the different phosphorus form concentrations are major in the high evasion , but the first sediment that arrives has the greater concentration of particles < 2 μm. The surface sediment has a low phosphorus retention capacity. The surface water analyzed show the presence of active principle of imidacloprid, atrazina, simazine and clomazone mainly the ones collected close to tobacco farming. The active principles chlorpyrifos and imidacloprid were found in water that is designated to human consumption. This hydrographic watershed studied was considered a sick environment that needs actions to reduce the environmental impact generated from tobacco production